Quaternary ammonium silane-functionalized, methacrylate resin composition with antimicrobial activities and self-repair potential - Gong, Shi-qiang (2012)
Design of antimicrobial polymers for enhancing healthcare issues and minimizing environmental problems is an important endeavor with both fundamental and practical implications. Quaternary ammonium silane-functionalized methacrylate (QAMS) represents an example of antimicrobial macromonomers synthesized by a sol-gel chemical route; these compounds possess flexible Si-O-Si bonds. In present work, a partially-hydrolyzed QAMS copolymerized with bis-GMA is introduced. This methacrylate resin was shown to possess desirable mechanical properties with both a high degree of conversion and minimal polymerization shrinkage. Kill-on-contact microbiocidal activities of this resin were demonstrated using single-species biofilms of Streptococcus mutans (ATCC 36558), Actinomyces naeslundii (ATCC 12104) and Candida albicans (ATCC 90028). Improved mechanical properties after hydration provided the proof-of-concept that QAMS-incorporated resin exhibits self-repair potential via water-induced condensation of organic modified silicate (ormosil) phases within the polymerized resin matrix.